Review of Micro, Small, and Medium Enterprises (MSMEs) of Arunachal Pradesh - Nending Koka; Ratan Kaurinta (Dera Natung Government College Research Journal)
Micro, Small, and Medium Enterprises (MSMEs) constitute an important segment of the economy in terms of their contribution to generating employment opportunities, industrial production, creation of an entrepreneurship base, and maintaining an appreciable growth rate. The MSME sector has often been termed the engine of growth for developing economies. In Arunachal Pradesh MSME sector has a huge contribution to the economy in terms of providing employment opportunities, promoting equitable economic growth, decreasing regional disparities, and enhancing export potential. Arunachal Pradesh is a tribal economy, and the contribution of MSME to the economy is quite remarkable. This paper evaluates the current scenario of the MSME sector of Arunachal Pradesh and also attempts to focus on the increase in registered MSMEs in the past five-year period. The study is a review that was conducted with the help of secondary data retrieved from MSME Annual Reports, other government reports, newspapers, and research papers.